The relationship between psychosocial health and prenatal attachment in pregnant women - Bakır, Nazife; Sarızayim, Şule (Perinatal Medicine Foundation, 2020)
Objective The aim of this study is to determine the relationship between psychosocial health and prenatal attachment in pregnant women. Methods This quantitative and descriptive study was conducted with 241 pregnant women who admitted to the Obstetrics and Gynecology Clinic of a state hospital in the Mediterranean Region between December 2019 and March 2020. The Introductory Characteristics Form, Prenatal Psychosocial Health Assessment Questionnaire and Prenatal Attachment Inventory were used to collect the data. Results It was found in the study that 84.9% of the pregnancies were planned, 83.8% of them were at the last trimester, and 31.3% of them were their first pregnancy. The mean score of pregnant women was 4.54±0.18 (range: 3.87 to 4.87) in the Prenatal Psychosocial Health Assessment Questionnaire and 72.24±7.48 (range: 50.00 to 84.00) in the Prenatal Attachment Inventory. It was found that the mean scores obtained in the Prenatal Psychosocial Health Assessment Questionnaire were significantly different between the groups according to age, education level, family type and number of pregnancy. There was also significant difference in the mean scores obtained in the Prenatal Attachment Inventory between the groups according to age, education level, family type, number of child and household income level. Conclusion We did not find any statistically significant correlation between the scores of the Prenatal Psychosocial Health Assessment Questionnaire and the Prenatal Attachment Inventory in our study.